2014
DOI: 10.2298/jsc010413080m
|View full text |Cite
|
Sign up to set email alerts
|

The application of NIR spectroscopy with chemometric analysis for monitoring the powder blending process

Abstract: This paper reports the use of near infrared (NIR) spectroscopy as a process analytical technology (PAT) tool for monitoring the metformin (N,N--dimethylimidodicarbonimidic diamide) hydrochloride and poly(vinyl pyrrolidone) (PVP) mixing process, which is the first stage in tablet production. Blend homogeneity was tested using the non-invasive NIR spectroscopy method and the partial least squares (PLS) regression model was applied for the analysis of the obtained spectra. Simultaneously, the critical parameter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Liu et al 35 introduced a new approach (Vector operation moving block standard deviation), to characterize the powder blend uniformity of Angongnuihuang pills immediately. Additionally, Ljiljana et al 36 reported the usage of NIRS as a process analytical technology for monitoring the mixing process of metformin hydrochloride and vinylpyrrolidone. It could be concluded that the proposed technique will be an effective tool for the critical manufacturing step in the solid dosage form.…”
Section: Nir Spectroscopymentioning
confidence: 99%
“…Liu et al 35 introduced a new approach (Vector operation moving block standard deviation), to characterize the powder blend uniformity of Angongnuihuang pills immediately. Additionally, Ljiljana et al 36 reported the usage of NIRS as a process analytical technology for monitoring the mixing process of metformin hydrochloride and vinylpyrrolidone. It could be concluded that the proposed technique will be an effective tool for the critical manufacturing step in the solid dosage form.…”
Section: Nir Spectroscopymentioning
confidence: 99%